2014
DOI: 10.1158/1078-0432.ccr-13-0556
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2 Is a Potential Therapeutic Target and Biomarker in Alveolar Rhabdomyosarcoma Harboring the PAX3–FOXO1 Fusion Gene

Abstract: Purpose Alveolar rhabdomyosarcoma that harbors the PAX3/FOXO1 fusion gene (t-ARMS) is a common and lethal subtype of this childhood malignancy. Improvement in clinical outcomes in this disease is predicated upon the identification of novel therapeutic targets. Experimental Design Robust mouse models were used for in vivo analysis, and molecular studies were performed on xenografts treated in parallel. Two independent patient sets (n=101 and 124) of clinically-annotated tumor specimens were used for analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…4D). Using an index of skin toxicity previously reported, [40] there was a slight decrease in the cumulative toxicity in the combination treatment arm of this study compared to 10 Gy XRT alone (Fig. 4E).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…4D). Using an index of skin toxicity previously reported, [40] there was a slight decrease in the cumulative toxicity in the combination treatment arm of this study compared to 10 Gy XRT alone (Fig. 4E).…”
Section: Resultssupporting
confidence: 59%
“…Inhibition of TORC1 has been associated with increased sensitivity to XRT, and it was considered that rapamycin‐induced G1 arrest could contribute to the sensitizing effects. We also showed that AZD8055 could enhance the effect of XRT, and that FANCD2 was regulated downstream of TORC1 in part by S6K1/2 activity . It was therefore of interest to determine whether selumetinib could enhance daily fractionated XRT.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent preclinical data have shown that FANCD2 is a potential therapeutic target in fusion-positive alveolar rhabdomyosarcoma. In mouse models, FANCD2 may have a significant role in the radiation resistance of alveolar rhabdomyosarcoma, and offers a possibility for targeting this DNA repair protein through mTOR inhibition [ 7 ]. Targeting of the fusion protein is an area of active research from multiple directions; Jothi et al .…”
Section: Advances In Biologymentioning
confidence: 99%
“…For instance, it may happen from lung cancer (3). Many biomarkers are assigned for rhabdomyosarcomas (4,5). The identification of the tumor major proteins can be helpful to better understand the muscle cancer mechanisms.…”
Section: Introductionmentioning
confidence: 99%